Supplement inclusion on post-weaning foals’ (Mangalarga Marchador) diet with a protein supplement based on whey protein, glutamine, and lysine - Pierre Barnabé Escodro; Mário Fernando Vilela de Almeida; Tobyas Maia de Albuquerque Mariz; Rebeca Alves Weigel; Yane Fernandes Moreira; Fatima Caroline Soares Borges; Amanda Caroline Gomes Graboschii; Luan Luthzemberg Ferreira de Andrade; Marcio Calixto Matias; Julimar do Sacramento Ribeiro (Semina: Ciências Agrárias, 2021)
The objective of this study was to evaluate the partial replacement effect on body measurements (body mass, muscle thickness, and fat thickness) of the concentrated fraction of foals’ diet with a protein supplement containing whey protein, glutamine, and lysine during the post-weaning period. Eighteen Mangalarga Marchador foals were randomly divided into two groups in the post-weaning phase, with nine animals each in the control group (CG) and the group receiving protein supplementation (WG). Based on 4% of their body weight (BW), the CG animals received a diet with roughage to concentrate in a ratio of 50:50, which composed of Cynodon sp. hay and a 15% crude protein (CP) commercial horse ration. The WG diet consisted of the same amount of hay used for the CG diet, half the amount of concentrate used in the CG diet, and 102 g of a protein supplement containing whey protein, glutamine, and lysine. During the experiment, five evaluations were performed, starting on the day of weaning (day 0), followed by evaluations conducted at 7, 14, 28, and 42 days after weaning. Body measurements, body mass, and thickness of the fat and muscle layers were assessed at each time point. The substitution of a portion of the commercial diet with protein supplement containing whey protein, glutamine, and lysine did not cause changes in the weight gain or linear measurements of Mangalarga Marchador foals during the post-weaning period; however, the change in diet increased muscle thickness and decreased fat thickness when compared to animals in the control group.